Generalization of learned predator recognition in coral reef ecosystems: how cautious are damselfish?. (12th February 2013) - Mitchell, Matthew D.; McCormick, Mark I.; Chivers, Douglas P.; Ferrari, Maud C. O.; Costa, Daniel
Summary Learned predator recognition provides animals with an adaptive mechanism to rapidly adapt to current levels of predation risk. Prey may be able to reduce the cost associated with learning if they can use information learned about known predators to respond to cues from closely related predators with which they are unfamiliar. The capacity of prey to generalize recognition and distinguish between novel predators and non‐predators is poorly understood, particularly in species‐diverse communities with many closely related predators and non‐predators. Lemon damselfish, Pomacentrus moluccensis, conditioned to recognize the odour of a predatory moon wrasse, Thalassoma lunare, as a risky stimulus, were subsequently tested for their response to T. lunare and a range of closely related predators and non‐predators from within the Labridae family, a distantly related non‐predator and a saltwater control. Pomacentrus moluccensis displayed antipredator responses not only to T. lunare odour, but also generalized their recognition to congeneric T. amblycephalum and T. hardwicke odours. Recognition was not extended to other species within (Labridae; Coris batuensis and Halichoeres melanurus) or beyond (Pseudochromidae; Pseudochromis fuscus) the family. Individuals could not distinguish between the predator T. hardwicke and non‐predator T. amblycephalum when generalizing their recognition to congeneric species based on chemosensory assessment alone. Our results demonstrate that reef fishes may limit their generalization to congeneric species only, and may be unable to distinguish between predators and non‐predators using chemosensory cues. Recognition patterns may result from uncertainties in predicting the identities of predators in species‐diverse communities.